PUNCHING CALCULATION OF REINFORCED CONCRETE FLOOR SLABS - E. K. Agakhanov; D. S. Kostenko; G. M. Kravchenko; E. V. Trufanova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Abstract. In this paper is considered the modeling of a monolithic reinforced concrete buildings structures by the spatial plate-core scheme and study of the floor slabs punching problem. When creating the finite element model of the building structure the floor slabs were created by four-node quadrilateral finite elements with 24 degrees of freedom, the columns and beams were created by spatial rods with 12 degrees of freedom. The calculation of the frame has been done by the software complex «SCAD», are got the efforts in the framework elements and are determined the concentration of stresses in the connections of slabs and columns. The program «Calculation of floor slab on punching» has been developed by the high-level language Object Pascal in Delphi environment, in accordance with the design standard which allows to research different locations of columns and stiffening diaphragms on the floor slab. The ratio of bearing capacity of the slab was calculated by means of the software «Calculation of floor slab on punching». Results are well correlated with the program «Arbat» of the software complex «SCAD». Difference of the developed program is in the possibility of considering of the columns and stiffness diaphragm location options on the floor slab (central, edge, corner). Program «Calculation of floor slab on punching» is recommended for use in the design of monolithic reinforced concrete structures.